Squarified Treemaps - Mark Bruls; Kees Huizing; Jarke van Wijk (Data Visualization'00: Proceedings of the Joint Eurographics - IEEE TCVG Symposium on Visualization, 2000)
An extension to the treemap method for the visualization of hierarchical information, such as directory structures and organization structures, is presented. The standard treemap method often gives thin, elongated rectangles. As a result, rectangles are difficult to compare and to select. A new method is presented to generate lay-outs in which the rectangles approximate squares. To strenghten the visualization of the structure, shaded frames are used around groups of related nodes.